2022
DOI: 10.3390/ijerph19137594
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems and 6-Sulfatoxymelatonin as Possible Predictors of Symptom Severity, Adaptive and Maladaptive Behavior in Children with Autism Spectrum Disorder

Abstract: In children with autism spectrum disorder (ASD), sleep disturbances are a frequent comorbidity with an adverse effect on their behavior and functioning. It was suggested that melatonin deficit is at least partly responsible for the sleep problems. The study aimed to investigate, in a sample of 56 children with ASD aged 2.8–13.3 years, if the sleep problems and melatonin secretion can serve as predictors of adaptive functioning and severity of the ASD core symptoms. We demonstrated that, after adjustment for ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…In line, Tordjman et al (2005) showed that nocturnal levels of 6-sulphatoxymelatonin (6-SM), a urinary melatonin metabolite closely correlated to pineal melatonin secretion, were negatively correlated to ASD symptom severity (deficits in verbal communication and play), a set of findings later replicated by the group (Tordjman et al, 2012). Subsequent studies exploring the predictive power of 6-SM on ASD symptom severity report varying results, where Babinska et al (2019) described no correlation between nocturnal 6-SM secretion and symptom severity, whereas Bartakovicova et al (2022) corroborated the results from Tordjman et al's study by finding a negative correlation between 6-SM secretion levels and symptom severity, after adjusting for age (Figure 3). Thus, these studies suggest that disrupted circadian rhythms, specifically through abnormal melatonin circadian function, may have an impact on ASD pathogenesis.…”
Section: Circadian Disruption As a Predictor Of Symptomsmentioning
confidence: 99%
“…In line, Tordjman et al (2005) showed that nocturnal levels of 6-sulphatoxymelatonin (6-SM), a urinary melatonin metabolite closely correlated to pineal melatonin secretion, were negatively correlated to ASD symptom severity (deficits in verbal communication and play), a set of findings later replicated by the group (Tordjman et al, 2012). Subsequent studies exploring the predictive power of 6-SM on ASD symptom severity report varying results, where Babinska et al (2019) described no correlation between nocturnal 6-SM secretion and symptom severity, whereas Bartakovicova et al (2022) corroborated the results from Tordjman et al's study by finding a negative correlation between 6-SM secretion levels and symptom severity, after adjusting for age (Figure 3). Thus, these studies suggest that disrupted circadian rhythms, specifically through abnormal melatonin circadian function, may have an impact on ASD pathogenesis.…”
Section: Circadian Disruption As a Predictor Of Symptomsmentioning
confidence: 99%
“…Melatonin is enzymatically degraded in the liver to 6-hydroxymelatonin and excreted in the urine as 6-sulfatoxymelatonin [32]. Several studies have shown that nocturnal levels of 6-sulfatoxymelatonin are significantly reduced in association with autism [33,34], likely due to impaired melatonin synthesis in the pineal gland. Melatonin is synthesized in the pineal gland from serotonin, through the addition of both an acetyl group and a methyl group.…”
Section: Introductionmentioning
confidence: 99%
“…ASD is characterized by core symptoms that include problems in social communication and interaction, as well as restricted repetitive patterns of behavior, activities or interests [3]. In addition to these behavioral characteristics, children with ASD typically suffer from a wide range of somatic problems at a higher rate than their neurotypical counterparts, e.g., feeding and gastrointestinal disorders [4,5], immunological disturbances [6], sleep disorders [7], neurological diseases and a variety of others [8,9]. Oxidative stress, implicated in the pathophysiology of multiple disorders, has been shown to be a common denominator of neurodevelopmental diseases including ASD [10][11][12].…”
Section: Introductionmentioning
confidence: 99%